STUDI PEMAHAMAN MAHASISWA SEKOLAH TINGGI ILMU KESEHATAN (STIKes) MUHAMMADIYAH PALEMBANG TERHADAP MATA KULIAH AL-ISLAM - Markinis Markinis (Conciencia, 2014)
Abstract: The approach used in this study is a mixed methods research is the use of both quantitative and qualitative approaches. While the study sample and research informants were 145 students drawn from the 5 courses, and 6 lecturers who taught courses in Al-Islam. The technique of collecting data; observation, documentation, testing, and interviews. While the analysis of the data processed in 2 ways, quantitative data processing using qualitative descriptive statistics. The qualitative data processing flow is analyzed through three activities: data reduction, data presentation and data verification / conclusion and used for descriptive answers based on data from interviews, observation, and documentation.     Based on the results of research and discussion, First, understanding student College of Health Sciences (STIKes) Muhammadiyah Palembang against al-Islam subjects who have test scores understanding of the subject of Al-Islam who answer the test and is included in the low category yatiubmulai of 59-0 or the value of C as much as 4 students (5%), as many as 10 students (10%) in the medium category ranging from the 79-60 or the value of B, while 131 people (85%) in the high category, ranging from 80- 100 or the value of A. Therefore, the student's understanding College of Health Sciences (STIKes) Muhammadiyah Palembang on subjects al-Islam overall good student understanding. Second, the factors that affect student understanding College of Health Sciences (STIKes) Muhammadiyah Palembang against al-Islam courses supporting factors include learning methods, facilities and infrastructure as well as learning media. While the inhibiting factors include the allocation of time, classroom situation and ability are not the same. Keywords: Understanding Students, Subjects Al-Islam